Penerapan Soft System Methodology untuk Model Konseptual Tingkat Pemahaman Implementasi Management Strategik Berbasis Administrasi Kontrak Dalam Peningkatan Profit Perusahaan Konstruksi - Gita Puspa Artiani; Nilam Tantri; Hendrik Sulistio (Sekolah Tinggi Teknik - PLN, 2022)
The construction world in Indonesia is currently growing rapidly, the competition conditions in the construction world today to get tighter. However, this condition can be a serious threat to the inadequate construction industry and company personnel unpreparedness, especially for project managers in dealing with problems and uncertainties caused by the high level of risk and complexity of the project, so that it can cause a high level of project failure which has an impact on decreasing company profits, so it can cause a high level of project failure which has an impact on decreasing company profits. Some causes that must be addressed include weak project management competence, lack of strategic management understanding based on contract administration by project managers and organizational culture that tends to be reactive. The main purpose of this research is to obtain an overview for the latest form of modeling developments that can be used as a model to see effect of strategic management implementation level based on contract administration by project managers on company performance in an effort to increase company profits. By using Soft System Methodology (SSM), a conceptual model has been built to describes a relationship between understanding level of strategic management implementation based on contract administration on company performance in an effort to increase company profits. Through the steps of SSM implementation has prepared an action plan to be taken, namely, strategic management planning that supports mission, strategies and organization goals